UniMAP's e-vehicles services - Allinie Mirna Abdul Malek
UniMAP's e-vehicle services is a system that provides vehicles booking services for Universiti Malaysia Perlis's (UniMAP) staffs and students. By implementing UniMAP's e-vehicle services, the objectives of this project which are to assist the UniMAP's Development Department in making the vehicles booking system more systematic and easy to handle as well as to simplify staffs and students in booking vehicles for University purposes achieved.